Proceedings of the 17th Symposium on Software Engineering for Adaptive and Self-Managing Systems 2022
DOI: 10.1145/3524844.3528056
|View full text |Cite
|
Sign up to set email alerts
|

Taming model uncertainty in self-adaptive systems using bayesian model averaging

Abstract: Research on uncertainty quantification and mitigation of softwareintensive systems and (self-)adaptive systems, is increasingly gaining momentum, especially with the availability of statistical inference techniques (such as Bayesian reasoning) that make it possible to mitigate uncertain (quality) attributes of the system under scrutiny often encoded in the system model in terms of model parameters. However, to the best of our knowledge, the uncertainty about the choice of a specific system model did not receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…We also plan to investigate how to include into the SHA model other multi-disciplinary cognitiverelated aspects and conduct variability model analysis. We want to mitigate uncertain (quality) attributes of the system under scrutiny and of the SHA model itself, especially with the availability of statistical inference techniques, such as Bayesian reasoning [7]. We would like to provide formal guarantees also for ethics-related concerns while designing, developing, deploying, and executing HMT systems.…”
Section: Future Plansmentioning
confidence: 99%
“…We also plan to investigate how to include into the SHA model other multi-disciplinary cognitiverelated aspects and conduct variability model analysis. We want to mitigate uncertain (quality) attributes of the system under scrutiny and of the SHA model itself, especially with the availability of statistical inference techniques, such as Bayesian reasoning [7]. We would like to provide formal guarantees also for ethics-related concerns while designing, developing, deploying, and executing HMT systems.…”
Section: Future Plansmentioning
confidence: 99%
“…We designed and carried out an experimental campaign 4 to evaluate our approach to risk-driven test case generation and diversity analysis. We executed multiple runs of the generation process by using different search approaches.…”
Section: B Design Of the Evaluationmentioning
confidence: 99%
“…Recent empirical studies found offline testing is less effective in uncovering safety violations compared to online testing [3]. Clearly, even if the ML components are reliable, they are embedded in complex and dynamic operational ecosystems affected by sources of uncertainty that may lead to unsafe component interactions and, therefore, to accidents [4], [5]. Online testing methods for ML-enabled systems deal with these issues by considering the ML components in a closed loop with the other parts and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…2), we say the robot is dependable. Dependability and other phenomena of interest, such as fatigue of the human agents and the outcome of the competition, are typically affected by uncertain and changing factors that shall be measured during the mission [5], [6]. Thus, both the robot and the human agents are equipped with sensors gathering information about their current state; specifically measuring their position inside the layout, the robot's level of charge, and the humans' level of muscular fatigue, which provides a measure of the physical effort they are currently enduring.…”
Section: Illustrative Examplementioning
confidence: 99%